John Herbert Corning papers - Corning, John Herbert, -approximately 1940.
Correspondence, poetry, programs, sketches, and photographs relating chiefly to the theater. Persons represented include Blanche Bates, Eleanor Robson Belmont, Reginald De Koven, Minnie Maddern Fiske, Victor Herbert, E.H. Sothern, and John Greenleaf Whittier. Includes autographs of Edwin Booth and Henry W. Longfellow.
Historian.
Collection material in English.
Keywords: Bates, Blanche, -- 1873-1941.; Belmont, Eleanor Robson, -- 1879-; Booth, Edwin, -- 1833-1893.; De Koven, Reginald, -- 1859-1920.; Fiske, Minnie Maddern, -- 1865-1932.; Herbert, Victor, -- 1859-1924.; Longfellow, Henry Wadsworth, -- 1807-1882.; Sothern, E. H. -- 1859-1933.; Whittier, John Greenleaf, -- 1807-1892.; Theater; Historians